Model Antropologis Menurut Stephen B. Bevans dan Relevansinya Bagi Mahasiswa Perantauan Di Kota Malang - Jie, Marcelino Bramantyoko (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2023)
This study discusses the cultural encounters of Catholic students who migrate to Malang City. This type of research is quantitative research by distributing questionnaires via Google Forms. The author discusses this theme from the perspective of the anthropological model according to Stephen B. Bevans. This study found that the culture shock experienced by overseas students towards the community in Malang City was mostly in the moderate category. The results of this research also found that there is a positive and significant relationship between overseas students and the community in Malang City. In general, people in Malang City will accept the presence of overseas students who come. Although there are still a number of views held by overseas stu as outsiders or outside groups, as long as there are good communication relationships, this view will change. This study provides recommendations for overseas students regarding the need to increase more intense interaction with the surrounding community through daily dialogue.